Integrating Group Dynamics Into Technopark Rice-Fish Farming Management: Strategies And Outcomes - Ramli, Isni Radifa; Almaghfiro, Elfira Zidna; Aqila, Fairuza (Universitas Galuh, 2025)
This study explores group dynamics in the management of Technopark Rice-Fish Farming, focusing on role distribution, effective communication, conflict resolution, and inclusive decision-making. Employing a qualitative method with an interpretivist approach, the research delves into the personal and social experiences of stakeholders in Dusun Samberembe, Sleman—an iconic Rice-Fish Farming site in Indonesia utilizing the jajar legowo method. Data were collected through field observations and interviews with management teams, youth organizations, and the local community, then analyzed to produce findings of significant relevance. The findings reveal that group dynamics play a pivotal role in promoting sustainability and productivity at Technopark Rice-Fish Farming. Collaboration across takeholders has facilitated the integration of technology and local resources, overcoming challenges such as differing visions, missions, and climate change impacts. Notably, the integration of technological and social approaches has boosted productivity by up to 30% compared to conventional methods. This study highlights that the strength of group dynamics extends beyond productivity gains to the human connections forged among individuals. The study also emphasizes that the strength of group dynamics extends beyond productivity, fostering solidarity and human connections that serve as a foundation for addressing challenges and driving sustainable innovation. These insights offer valuable implications for the management of other integrated agricultural systems.